Quantifying stem discoloration and decay following pruning and thinning an Acacia hybrid plantation. Issue 2 (30th November 2016) - Trang, T. T.; Glen, M.; Eyles, A.; Ratkowsky, D.; Beadle, C.; Mohammed, C.
Summary: Acacia hybrid ( Acacia mangium  ×  A. auriculiformis ) is widely planted in Vietnam, and part of the estate is managed for solid timber products. This requires pruning and thinning – practices that through mechanical wounding can facilitate the entry of fungal organisms, leading to stem defects. The extent to which this happens in Acacia hybrid has not been previously studied in Vietnam. A destructive survey was conducted in a 3‐year‐old Acacia hybrid plantation at Nghia Trung in Binh Phuoc province, 18 months after the imposition of pruning and thinning treatments. Pruned trees had a higher incidence and severity of discoloration and decay in the stem than unpruned trees; thinning increased the incidence of stem decay and the severity of discoloration but not the severity of decay. An interaction between pruning and thinning did not influence the incidence of stem decay but did increase the severity of discoloration in thinning treatments. Across treatments, levels of discoloration and decay were <30% and <5%, respectively. Modification of current pruning practices may be necessary to ensure that decay levels are kept within acceptable limits at an anticipated harvest age of 7–8 years.